2011
DOI: 10.1093/pcp/pcr121
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol Transport and Mannitol Dehydrogenase Activities are Coordinated in Olea europaea Under Salt and Osmotic Stresses

Abstract: The intracellular accumulation of organic compatible solutes functioning as osmoprotectants, such as polyols, is an important response mechanism of several plants to drought and salinity. In Olea europaea a mannitol transport system (OeMaT1) was previously characterized as a key player in plant response to salinity. In the present study, heterotrophic sink models, such as olive cell suspensions and fruit tissues, and source leaves were used for analytical, biochemical and molecular studies. The kinetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 71 publications
3
64
0
2
Order By: Relevance
“…toxicity which can ultimately disrupts K ? uptake by root cells, and exerts severe toxic effects on enzymes at the genetic level and thus, causing impairment in normal plant metabolism (Conde et al 2011). Shahbaz et al (2013) have observed decrease in K ?…”
Section: Direct Effects Of Salinity Stress On Plantsmentioning
confidence: 99%
“…toxicity which can ultimately disrupts K ? uptake by root cells, and exerts severe toxic effects on enzymes at the genetic level and thus, causing impairment in normal plant metabolism (Conde et al 2011). Shahbaz et al (2013) have observed decrease in K ?…”
Section: Direct Effects Of Salinity Stress On Plantsmentioning
confidence: 99%
“…In olive, it is reported that salinity stress tolerance involves both production and transport of mannitol through mannitol transport system (OeMaT1) gene expression (Conde et al 2011). This clearly means that both synthesis and transport of mannitol are equally important in imparting salinity stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of soil salinity stress on plants is a complex phenomenon with major consequences like hyperosmotic stress, ion cytotoxicity (mostly due to Na ? , Cl -and SO 4 -), nutritional imbalance and oxidative stress, which causes a series of changes at physiological, biochemical and molecular level (Conde et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto ha sido observado en el cultivo de Olea europea con un significativo incremento del crecimiento y proliferación de brotes (García et al 2002;Conde et al 2011). Así también, el tipo de agente osmótico y fuente de carbono usado influirá sobre la recuperación posterior de los explantos ya que tendrá un efecto evidente en la tasa de crecimiento (Gollagunta et al 2005).…”
Section: Enraizamientounclassified